SHIFTING FROM THE ROAD OF RUIN TO THE PATH OF PROSPERITY THROUGH COMMUNITY PARTICIPATION IN WATERHSED MANAGEMENT - Agnihotri, Y.; Samra, J.S. (Journal of Soil and Water Conservation, 2022)
State based programmes on Natural Resource Management were started more than a century back hi India. Lot of public funds were spent on the programmes each year but no commensurate results were obtained, as the local communities were not taken into confidence. It has, however, been, lately realized that no such progranuneme can ever achieve the desired success until and unless the communities are not involved.The paper narrates as to how an economically backward village called Relmajra' in Shivalik foothills of Punjab, treading the roads of ruin has been put on the path of prosperity through a Watershed Management Programmeme run with the help of village community. The village has now ushered in the era of plenties, generating a lot of individual income and social wealth.For achieving community participation it is however imperative that a `Catalyst' be identified and developed through the natural resource management programmeme, around which the village economy may revolve.